The realism - Vargas Huanca, Georgette (2020)
If once when you were a child, you climbed a ladder and fell, this episode probably put off any interest in trying as an infant in your life. You may have thought in your mind that the stairs were too high or short, big or ugly, and even bad. In materialistic terms it can be argued that all these series of characteristics associated with the ladder are thought from a subjective level, an idealistic and emotional notion that is engrossed in what feels like fear due to trauma. In contrast, a more objectivist vision would have to accept that the stairs are inanimate beings, useful objects for knowledge, but that they do not intentionally participate in the subject's sensitive experience. This last analysis is based on a philosophical trend called realism.